Theory and Meditation of Confucian Mindfulness: Analysis Based on the Concept of Vigilance in Solitude in Chinese Confucianism - Peng, Yanqin (Journal of religion and health, 2023)
Mindfulness has become an area of great interest in Western psychology, but it has been criticized for its de-religionization. Based on Chinese Confucianist Liu Zongzhou’s concept of shendu (慎独; vigilance in solitude), this study attempts to present a complete overview of the Confucian mindfulness meditation system from the theoretical basis and training method. The unique value of Confucian mindfulness meditation is that it directly points to morality, which can make up for the deficiency of mindfulness in Western psychology. Furthermore, Confucian mindfulness meditation can provide more suitable training methods for individuals who are culturally Chinese.